PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MATERI LOGIKA MATEMATIKA PADA SISWA KELAS X SEMESTER 2 SMA SWASTA ALSIORA ENDE TAHUN PELAJARAN 2015/2016 - Maria Oldiana T. Gette (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2018)
Based on observations in Private School Alsiora Ende in general there are many teachers apply learning that conventional. This resulted in low student learning, is therefore required capabilities as pengelolah classroom teachers to implement creative teaching methods to encourage students' interest in learning mathematics. One is the type cooperative learning of Jigsaw.This type of research is an experimental research with a quantitative approach. The population in this study were all students of class X SMA Private Alsiora as many as 125 students and sample in this research is class X3 as many as 20 students. The instrument used is a matter of describing the test as many as three items and analytical techniques used is the technique of analysis of covariance with product moment correlation formula.The results of the preparation of the learning is done produced good learning tools for meeting the requirements of validity, reliability and sensitivity. Learning tools include: Learning Implementation Plan (RPP), Student Worksheet (LKS), and test results for Learning (THB). Analysis of the results of Covariance (Anacova) provide significant value (F-count> F-table). This shows JIGSAW cooperative learning can improve learning outcomes mathematical logic mathematics especially the material in class X 2nd half Alsiora Ende Private High School Academic Year 2015/2016